Exploration of Newtonian Heating, Viscous Dissipation Effects on MHD Mixed Convection Flow of Williamson Fluid Against Radially Stretched Penetrable Wedge: A Numerical Study - Hussain, Majid; Ashraf, Mehwish; Ranjha, Qasim A. A.; İnç, Mustafa; Jahan, Shah (World Scientific Publ Co Pte Ltd, 2023)
An investigation on framing the features of Newtonian heating, suction/blowing, viscous dissipation on magneto hydrodynamic mixed convective Williamson fluid flow over a porous stretching wedge that is influenced by thermal radiation. The con-temporary model is employed to simulate the non-Newtonian behavior of fluid over porous wedge which stretches faster or slower than free stream velocity. Practical applications of wedge flow are drug delivery, cancer treatment, biotechnology and biomedicine. Initially, the major partial differential equations are transformed into ordinary differential equations via a suitable set of similarity transformation and then solved by the developed bvp4c algorithm in MATLAB. A comprehensive analysis of definite parameters on the profiles of velocity, temperature, Nu(loc), and skin friction coefficient is explained and scrutinized. The results indicate that elaboration in M and We shows a decline in velocity profile at R=1.6 but an opposite trend for R=0.4. However, temperature increases for both R=1.6/0.4. Furthermore, (at R=0.4), an augmentation in Pr results in uphill local Nusselt number. The consequences of the present exploration are compared with the existing works in specific situations and more agreement has been perceived.
Keywords: MHD flow; viscous dissipation; Newtonian heating; radiation; Williamson fluid; numerical solution